2021
DOI: 10.3390/molecules27010117
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Plant Pollen Sources, Polyphenolic Compounds, Fatty Acids and Antioxidant/Antimicrobial Activity from Bee Pollen

Abstract: In this study, the botanical origin, total flavonoid and phenolic content, antioxidant activity, phenolic profile and fatty acid composition of mixed bee pollen loads collected in Bayburt, Turkey, were determined. In addition to these assays, antibacterial activity of bee-collected pollen extract (BCPE) against a variety of food-borne pathogenic bacteria was determined in vitro. Pollen loads were classified into five botanical families based on their color: Asteraceae, Fabaceae, Campanulaceae, Cistaceae and Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
4
32
2
Order By: Relevance
“…Chromatographic results also revealed that Moroccan bee pollen samples contained four phenolic acids—caffeic acid ( m/z 179), caffeic acid hexoside ( m/z 341), p -coumaric acid ( m/z 163), and p -coumaric acid hexoside ( m/z 325)—at low concentrations in BP1, BP2, BP5, and BP8. Such phenolic acids have a wide distribution in the plant kingdom, and their presence has been associated with biological activities such as antiproliferative, antioxidant, and antimicrobial activities [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatographic results also revealed that Moroccan bee pollen samples contained four phenolic acids—caffeic acid ( m/z 179), caffeic acid hexoside ( m/z 341), p -coumaric acid ( m/z 163), and p -coumaric acid hexoside ( m/z 325)—at low concentrations in BP1, BP2, BP5, and BP8. Such phenolic acids have a wide distribution in the plant kingdom, and their presence has been associated with biological activities such as antiproliferative, antioxidant, and antimicrobial activities [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers agree that a single method is often not sufficient to quantify the potential activities of antioxidants, so employing antioxidant quantification assays based on different working principles is a necessary method of comprehensively evaluating the material under analysis [ 17 , 31 , 42 ]. Antioxidant results obtained from the current study demonstrated that some samples, such as BP4, BP5, BP6, and BP7, contain pollen species with potent free radical scavengers with minor reducing power activity.…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of pollen samples from different plant species collected from Bayburt, Turkey, were investigated for its phenolic and fatty acid content [ 48 ]. A total of 23 phenolics were quantified, represented by rutin (115.4 mg/kg) followed by kaempferol (9.8 mg/kg), quercetin (7.8 mg/kg), myricetin (2.2 mg/kg), and p-coumaric acid (0.5 mg/kg) [ 48 ].…”
Section: Phytonutrientsmentioning
confidence: 99%
“…Polyphenols have great importance, because they help the human body to fight against diseases. Determining the functions of foods or dietary supplements used as antioxidants has grown crucial, especially in recent years as the prevalence of several diseases such as cancer has increased (Gercek et al, 2021). Since phenolic chemicals have been acknowledged as potentially helpful taxonomic identifiers, there have been more investigations on their characterisation in pollen (Mosić et al, 2019).…”
Section: Nutritional Value Of Pollen Samplesmentioning
confidence: 99%